Leveraging Humanized Animal Models to Understand Human Drug Disposition: Opportunities, Challenges, and Future Directions. Issue 2 (28th November 2017) - Choo, Edna F.; Salphati, Laurent
Abstract : The utility of animal models in understanding drug disposition and extrapolating to human in a direct manner is limited, confounded by differences in enzyme and transporter substrate specificity and expression between species. Conversely, certain clinical pharmacology or mechanistic studies cannot be conducted for ethical and practical reasons. Thus, humanized animal models could be useful to bridge the gap between preclinical and clinical pharmacology and gain relevant insight into the determinants of drug disposition and drug–drug interaction (DDI).